Aircraft engine performance and integration in a flying wing aircraft conceptual design - Miao, Zhisong. (Cranfield University, 2012)
The increasing demand of more economical and environmentally friendly aero engines leads to the proposal of a new concept – geared turbofan. In this thesis, the characteristics of this kind of engine and relevant considerations of integration on a flying wing aircraft were studied. The studies can be divided into four levels: GTF-11 engine modelling and performance simulation; aircraft performance calculation; nacelle design and aerodynamic performance evaluation; preliminary engine installation. Firstly, a geared concept engine model was constructed using TURBOMATCH software. Based on parametric analysis and SFC target, the main cycle parameters were selected. Then, the maximum take-off thrust was verified and corrected from 195.56kN to 212kN to meet the requirements of take-off field length and second segment climb. Besides, the engine performance at offdesign points was simulated for aircraft performance calculation. Secondly, an aircraft performance model was developed and the performance of FW-11 was calculated on the basis of GTF-11 simulation results. Then, the effect of GTF-11 characteristics performance on aircraft performance was evaluated. A comparison between GTF-11 and conventional turbofan, RB211- 524B4, indicated that the aircraft can achieve a 13.1% improvement in fuel efficiency by using the new concept engine. Thirdly, a nacelle was designed for GTF-11 based on NACA 1-series and empirical methods while the nacelle dimensions of conventional turbofan RB211-525B4 were obtained by measure approach. Then, the installation thrust losses caused by nacelle drags of the two engines were evaluated using ESDU 81024a. The results showed that the nacelle drags account for about 4.08% and 3.09% of net thrust for GTF-11 and RB211-525B4, respectively. Finally, the considerations of engine installation on a flying wing aircraft were discussed and a preliminary disposition of GTF-11 on FW-11 was presented.
Keywords: Geared Turbofan; Simulation; Nacelle; Drag; Installation